Application for Introduction of Family Medicial Plants Typical of North Sulawesi Using Augmented Reality Technology - Mangente, Geybi Beatrice; Tulenan, Virginia; Sugiarso, Brave A. (Jurnal Teknik Informatika, 2021)
Abstract — Family medicinal plants (abbreviated as TOGA) are home-grown plants that are efficacious as medicines. Cultivation of medicinal plants for families (TOGA) can spur small and medium-sized businesses in the field of herbal medicines even if done individually. Each family can cultivate medicinal plants independently and utilize them so that there will be a principle of self-reliance in the treatment of the family. Designed an application for the introduction of family medicinal plants using augmented reality using the display of the application using 3-dimensional animation (3D) to make it look more interesting and make the public more interested in getting to know and know the family medicinal plants in North Sulawesi that the community is beginning to forget. This study using multimedia development life cycle ( MDLC) animation and objects in the form of 3 dimensions (3D) This research aims to build multimedia applications that can introduce family medicine plants in north Sulawesi using augmented reality technology. The results of the testing of the question and answer that has been done in the community through the questionnaire that has been answered correctly are 90% about the introduction of family medicinal plants about the types of family medicinal plants as well as the benefits and ways of fuming after the community uses the application of the introduction of family medicinal plants in north Sulawesi using augmented reality technology.Keywords: Augmented Reality; Multimedia Development Life Cycle; Smartphone; Plant Medicine Family.Abstrak— Tanaman obat keluarga (disingkat TOGA) adalah tanaman hasil budidaya rumahan yang berkhasiat sebagai obat. Budidaya tanaman obat untuk keluarga (TOGA) dapat memacu usaha kecil dan menengah di bidang obat-obatan herbal sekalipun dilakukan secara individual. Setiap keluarga dapat membudidayakan tanaman obat secara mandiri dan memanfaatkannya, sehingga akan terwujud prinsip kemandirian dalam pengobatan keluarga. Dirancanglah sebuah aplikasi pengenalan tanaman obat keluarga menggunakan augmented reality dengan menggunakan tampilan aplikasi menggunakan animasi 3 dimensi (3D) agar terlihat lebih menarik dan membuat masyarakat lebih tertarik mengenal serta mengetahui kembali tanaman obat keluarga di sulawesi utara yang mulai dilupakan masyarakat. Pada penelitian ini menggunakan metode Multimedia Development Life Cycle ( MDLC ) animasi dan objek berupa 3 dimensi (3D) Penelitian ini bertujuan untuk membangun aplikasi multimedia yang dapat mempekenalkan tanaman obat keluarga yang ada di sulawesi utara menggunakan teknologi augmented reality. Hasil testing dari tanya jawab yang telah dilakukan pada masyarakat melalui kuisioner yang telah diberikan menjawab dengan benar yaitu sebesar 90% mengenai pengenalan tanaman obat keluarga tentang jenis – jenis tanaman obat keluarga serta manfaat dan cara meramu setelah masyarakat menggunakan aplikasi pengenalan tanaman obat keluarga di sulawesi utara menggunakan teknologi augmented reality.Kata Kunci: Augmented Reality; Multimedia Development Life Cycle; Smartphone; Tanaman Obat Keluarga.